J. W. von Goethe - Weber, Friedrich, 1765-1811 (engraver):::Creator:::::::::::: (Karlsruhe; Germany; im. Kunst-Verlag. W. Creuzbauerin Carlsruhe)
Half-length full-face portrait of Johann Wolfgang von Goethe.